2020
DOI: 10.1002/adfm.202002643
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the Voltage Hysteresis of Li‐Rich Cathodes: Electrochemical Monitoring, Modulation Anionic Redox Chemistry and Theoretical Verifying

Abstract: Cathodes in lithium‐ion batteries with anionic redox can deliver extraordinarily high specific capacities but also present many issues such as oxygen release, voltage hysteresis, and sluggish kinetics. Identifying problems and developing solutions for these materials are vital for creating high‐energy lithium‐ion batteries. Herein, the electrochemical and structural monitoring is conducted on lithium‐rich cathodes to directly probe the formation processes of larger voltage hysteresis. These results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 57 publications
2
74
0
Order By: Relevance
“…Sun et al reported that the TM redox potential is determined by the energy gap between energy level of TM 3d -O 2p (or nonbonding O 2p ) and Li redox reactions. [49] As the energy gap changes with the Li/O ratio, the lower Li/O ratio in the LLC cathode results in a higher potential for some of the TM ions. The stacking faults originating from the excess Li could also lead to a lower reaction potential.…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al reported that the TM redox potential is determined by the energy gap between energy level of TM 3d -O 2p (or nonbonding O 2p ) and Li redox reactions. [49] As the energy gap changes with the Li/O ratio, the lower Li/O ratio in the LLC cathode results in a higher potential for some of the TM ions. The stacking faults originating from the excess Li could also lead to a lower reaction potential.…”
Section: Resultsmentioning
confidence: 99%
“…During subsequent discharge to 2 V, Mn ions partially move back to their original sites and then some vacancies are filled with inserted Li + . [3,22,23,27] As a result, the irreversible Mn migration would be inevitably accompanied by the occurrence of spinel cubic phase as presented in the gray ellipse circled in the XRD pattern discharged to 2 V (Figure 3a). By contrast, the coexistence of layered and spinel phases can be suppressed in SLNMO (Figure 3c), which would refrain the collapse of layered structures during cycling.…”
Section: Ex and In Situ Characterizations To Unveil The Function Of S...mentioning
confidence: 99%
“…In cathode materials of lithium‐ion batteries (LIBs), the irreversible migration of transition metal (TM) atoms is one of the origins causing structure degradation and performance deterioration. [ 1–4 ] For high‐nickel layered oxides, they suffer from a severer structure degradation of the rock salt phase with Li/Ni cation mixing, and cause the continuous sacrifice of high‐capacity layered structures with nucleation and growth. [ 5,6 ] This scenario infects another class of promising lithium‐rich manganese‐based cathode oxide Li 1.2 Ni 0.2 Mn 0.6 O 2 (LNMO), widely concerned by virtue of their high capacity of over 270 mAh g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Every element and stoichiometric ratio play a critical role in determining the whole structure and electrochemical activity [62] . Hua et al [63] systematically studied the relationship between Li content and the structure of Li x Ni 0.2 Mn 0.6 O y by matching the Li content with the precursor. When x < 0.4, the material was indexed to the spinel phase (Fd$$\bar 3$$m), while at 0.4 < x < 1.2, the material was a complex of the spinel (Fd$$\bar 3$$m) and rock salt (Fm$$\bar 3$$m) phases, including Li and the layered monoclinic phase (C2/ [60] .…”
Section: Ratio Of Ni Co Mn and Li/omentioning
confidence: 99%